The effect of entrepreneurial education and personality to the entrepreneurial intention through self-efficacy - Prastyaningtyas, Efa Wahyu; Soetjipto, Budi Eko; Rudijanto, Ery Tri Djatmika (MEC-J (Management and Economics Journal), 2019)
Entrepreneurial education, entrepreneurial personality and self-efficacy are variables that vastly affect the entrepreneurial intention. It is an effort to nurture students’ entrepreneurial intention of Teacher Training and Education Faculty at Nusantara PGRI University Kediri. This research aims to identify the indirect effect of entrepreneurial education and personality towards entrepreneurial intention through self-efficacy. The research sample is 151 students who received entrepreneurship course. The finding shows that entrepreneurial education and entrepreneurial personality affect the entrepreneurial intention through self-efficacy.